Pengukuran Kinerja Institusi dengan Pendekatan BSC (Balanced Scorecard) dan DEA (Data Envelope Analysis) Dalam Peningkatan Efisiensi Organisasi (Studi Kasus: Satuan Polisi Pamong Praja - Kabupaten Kampar, Provinsi Riau) - Bamatraf, Lutfia; Prabowo, Rony (Universitas Nusantara PGRI Kediri, 2024)
This research uses the Balanced Scorecard (BSC) and Data Envelopment Analysis (DEA) approaches to measure and improve the efficiency of Satpol PP performance. BSC provides a holistic perspective in measuring performance from various aspects such as finance, customers, internal business processes, and learning and growth. This type of research is descriptive research with a quantitative approach. Data was collected through observation, interviews and documentation from the Kampar Regency Satpol PP. The data collected was analyzed using BSC to identify Key Performance Indicators (KPI) in each perspective, then analyzed further using DEA to determine the relative efficiency of each work unit. Data processing was carried out with DEA-Solver software. The research results show that from a financial perspective, the efficiency of the Kampar Regency Satpol PP is 85%, with details that there are several areas that need to be improved to achieve maximum efficiency. The customer perspective shows a satisfaction level of 75%, which shows the need to improve service quality. The internal business process perspective indicates that 70% of operational processes run efficiently, while the learning and growth perspective shows a level of competency increase of 80%. The research results show that the Kampar Regency Satpol PP needs to make improvements in several areas to achieve optimal performance and efficiency. The recommended performance improvement strategy includes increasing human resource capacity through training, optimizing internal business processes, and improving the quality of services to the community. Keywords: performance, BSC, DEA, efficiency, Satpol